2022
DOI: 10.1007/s40744-022-00504-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Economic Benefit of Achieving Disease Control in Psoriatic Arthritis and Ankylosing Spondylitis: A Retrospective Analysis from the OM1 Registry

Abstract: Background: There is limited evidence on the clinical and economic benefit of achieving disease control in psoriatic arthritis (PsA) and ankylosing spondylitis (AS), thus we aimed to assess the impact of disease control on healthcare resource use (HCRU) and direct medical costs among US patients with PsA or AS over 1 year. Methods: Data were derived from the US OM1 PsA/AS registries (PsA: 1/2013-12/2020; AS: 01/2013-4/2021) and the Optum Insight Clin-formaticsÒ Data Mart to identify adult patients with PsA or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Management of AS is associated with significant economic burden by way of high direct medical costs (e.g., pharmacy, inpatient, outpatient, and emergency department [ED] visits) and increasing impairment of work and daily living abilities [ 5 ]. Indeed, retrospective claims database studies have demonstrated substantial all-cause medical costs, pharmacy costs, and overall health care resource utilization among patients with active AS [ 6 , 7 ]. Moreover, patients with greater disease severity at the time of treatment initiation and those not achieving disease control had significantly greater disease-associated costs than patients with milder disease or those who achieved disease control [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Management of AS is associated with significant economic burden by way of high direct medical costs (e.g., pharmacy, inpatient, outpatient, and emergency department [ED] visits) and increasing impairment of work and daily living abilities [ 5 ]. Indeed, retrospective claims database studies have demonstrated substantial all-cause medical costs, pharmacy costs, and overall health care resource utilization among patients with active AS [ 6 , 7 ]. Moreover, patients with greater disease severity at the time of treatment initiation and those not achieving disease control had significantly greater disease-associated costs than patients with milder disease or those who achieved disease control [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, retrospective claims database studies have demonstrated substantial all-cause medical costs, pharmacy costs, and overall health care resource utilization among patients with active AS [ 6 , 7 ]. Moreover, patients with greater disease severity at the time of treatment initiation and those not achieving disease control had significantly greater disease-associated costs than patients with milder disease or those who achieved disease control [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%